Is treatment in certified cancer centers related to better survival in patients with pancreatic cancer?: Evidence from a large German cohort study - Rößler, Martin; Schmitt, Jochen; Bobeth, Christoph; Gerken, Michael; Kleihues-van Tol, Kees; Reißfelder, Christoph; Rau, Bettina M.; Distler, Marius; Piso, Pompiliu; Günster, Christian; Klinkhammer-Schalke, Monika; Schoffer, Olaf; et al. (BMC cancer, 2022)
Treatment of cancer patients in certified cancer centers, that meet specific quality standards in term of structures and procedures of medical care, is a national treatment goal in Germany. However, convincing evidence that treatment in certified cancer centers is associated with better outcomes in patients with pancreatic cancer is still missing. We used patient-specific information (demographic characteristics, diagnoses, treatments) from German statutory health insurance data covering the period 2009-2017 and hospital characteristics from the German Standardized Quality Reports. We investigated differences in survival between patients treated in hospitals with and without pancreatic cancer center certification by the German Cancer Society (GCS) using the Kaplan-Meier estimator and Cox regression with shared frailty. The final sample included 45,318 patients with pancreatic cancer treated in 1,051 hospitals (96 GCS-certified, 955 not GCS-certified). 5,426 (12.0%) of the patients were treated in GCS-certified pancreatic cancer centers. Patients treated in certified and non-certified hospitals had similar distributions of age, sex, and comorbidities. Median survival was 8.0 months in GCS-certified pancreatic cancer centers and 4.4 months in non-certified hospitals. Cox regression adjusting for multiple patient and hospital characteristics yielded a significantly lower hazard of long-term, all-cause mortality in patients treated in GCS-certified pancreatic centers (Hazard ratio = 0.89; 95%-CI = 0.85-0.93). This result remained robust in multiple sensitivity analyses, including stratified estimations for subgroups of patients and hospitals. This robust observational evidence suggests that patients with pancreatic cancer benefit from treatment in a certified cancer center in terms of survival. Therefore, the certification of hospitals appears to be a powerful strategy to improve patient outcomes in pancreatic cancer care. ClinicalTrials.gov ( NCT04334239 ).